MEWUJUDKAN KESETARAAN GENDER MELALUI PENDIDIKAN ISLAM: TELAAH ATAS KEBIJAKAN RASULULLAH SAW TERHADAP PENDIDIKAN WANITA - Aisahrani Ritonga; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
The issue of gender equality in education has been an ongoing topic of discussion, including in the context of Islamic education. So far, there is an assumption that Islam limits women's freedom of movement, especially in obtaining education. This study aims to examine the policies of the Prophet Muhammad SAW on women's education as a form of reflection on the principle of gender equality in Islam. The main focus of this study is how the Prophet Muhammad SAW provided space and opportunities for women to access education, as well as its impact on the intellectual and social development of Muslim society in the early days of Islam. The research method used is a qualitative approach with a library research type. Data were obtained through a literature review of primary sources such as authentic hadiths, sirah nabawiyah, and relevant secondary literature on education in Islam and gender issues. Data analysis was carried out descriptively-critically in order to describe and interpret the practice of women's education during the time of the Prophet Muhammad SAW. The results of the study show that the Prophet Muhammad SAW actively encouraged and facilitated education for women, both in religious and social aspects. This is evidenced by the existence of educated female figures during his time, such as Aisyah RA who became a reference for knowledge for her companions. The Prophet's policies reflect the values ​​of equality, justice, and respect for women's rights in gaining knowledge. The conclusion of this study is that Islamic education truly upholds the principle of gender equality, as reflected in the practices and policies of the Prophet Muhammad SAW towards women's education.